Photochemical and thermal degradation of a naturally occurring dye used in artistic painting. A chromatographic, spectrophotometric and fluorimetric study on saffron - Vida Vickackaite; Aldo Romani; Danilo Pannacci; Gianna Favaro (International Journal of Photoenergy)
Saffron is a yellow substance which is extracted from the stigmas of Crocus sativus L. and is used in painting, cooking and medicine. In this paper six components (trans and cis crocins) with carotenoid structures were separated from natural saffron by HPLC and were characterised by their absorption and emission spectra. Photochemical and thermal processes which degrade the dye were also investigated. The effect of light promoted the cis ⇄ trans isomerization, while the thermal effect detached the glycosyl moieties.